Disability accrual in primary and secondary progressive multiple sclerosis - Harding-Forrester, Sam; Roos, Izanne; Nguyen, Ai-Lan; Malpas, Charles B; Diouf, Ibrahima; Moradi, Nahid; Sharmin, Sifat; Izquierdo, Guillermo; Eichau, Sara; Patti, Francesco; Horakova, Dana; Kubala Havrdova, Eva; et al. (Journal of neurology, neurosurgery, and psychiatry, 2023)
BACKGROUND: Some studies comparing primary and secondary progressive multiple sclerosis (PPMS, SPMS) report similar ages at onset of the progressive phase and similar rates of subsequent disability accrual. Others report later onset and/or faster accrual in SPMS. Comparisons have been complicated by regional cohort effects, phenotypic differences in sex ratio and management and variable diagnostic criteria for SPMS. METHODS: We compared disability accrual in PPMS and operationally diagnosed SPMS in the international, clinic-based MSBase cohort. Inclusion required PPMS or SPMS with onset at age ≥18 years since 1995. We estimated Andersen-Gill hazard ratios for disability accrual on the Expanded Disability Status Scale (EDSS), adjusted for sex, age, baseline disability, EDSS score frequency and drug therapies, with centre and patient as random effects. We also estimated ages at onset of the progressive phase (Kaplan-Meier) and at EDSS milestones (Turnbull). Analyses were replicated with physician-diagnosed SPMS. RESULTS: Included patients comprised 1872 with PPMS (47% men; 50% with activity) and 2575 with SPMS (32% men; 40% with activity). Relative to PPMS, SPMS had older age at onset of the progressive phase (median 46.7 years (95% CI 46.2-47.3) vs 43.9 (43.3-44.4); p<0.001), greater baseline disability, slower disability accrual (HR 0.86 (0.78-0.94); p<0.001) and similar age at wheelchair dependence. CONCLUSIONS: We demonstrate later onset of the progressive phase and slower disability accrual in SPMS versus PPMS. This may balance greater baseline disability in SPMS, yielding convergent disability trajectories across phenotypes. The different rates of disability accrual should be considered before amalgamating PPMS and SPMS in clinical trials.
Keywords: multiple sclerosis; postižení; Humans; Disease Progression; Persons with Disabilities; progrese nemoci; Proportional Hazards Models; lidé; Multiple Sclerosis; Multiple Sclerosis, Chronic Progressive; chronicko-progresivní roztroušená skleróza; roztroušená skleróza; proporcionální rizikové modely